Filling of simulated lateral canals with gutta-percha or thermoplastic polymer by warm vertical compaction - Sant'Anna-Junior, Arnaldo [UNESP]; Guerreiro-Tanomaru, Juliane M.aria [UNESP]; Martelo, Roberta B.osso [UNESP]; Silva, Guilherme F.erreira da [UNESP]; Tanomaru Filho, Mário [UNESP] (FapUNIFESP (SciELO), 2015)
The aim of this study was to evaluate the ability of gutta-percha and a thermoplastic synthetic polymer (Resilon) to fill simulated lateral canals, using warm vertical compaction. Forty-five single-rooted human teeth were prepared using the rotary crown-down technique. Artificial lateral canals were made at 2, 5, and 8 mm from the working length (WL) in each root. The specimens were divided into three groups (n = 15), according to the filling material: Dentsply gutta-percha (GD), Odous gutta-percha (GO), and Resilon cones (RE). The root canals were obturated using warm vertical compaction, without endodontic sealer. The specimens were subjected to a tooth decalcification and clearing procedure. Filling of the lateral canals was analyzed by digital radiography and digital photographs, using the Image Tool software. The data were subjected to the Kruskal-Wallis and Dunn tests at 5% significance. RE had the best filling ability in all root thirds (p < 0.05), with similar results for GO in the coronal third. In the middle and apical thirds, GD and GO had similar results (p > 0.05). Resilon may be used as an alternative to gutta-percha as a solid core filling material for use with the warm vertical compaction technique. The study findings point to the potential benefit of the warm vertical compaction technique for filling lateral canals, and the study provides further information about using Resilon and gutta-percha as materials for the warm vertical compaction technique.